2016
DOI: 10.13189/ujer.2016.041024
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perceptions on Senior High School Readiness of Higher Education Institutions in the Philippines

Abstract: The focused of this study is on the readiness of higher education institutions in the Philippines to the implementation of the Senior High School program of the new K-12 curriculum. Data were collected through a survey questionnaire. The findings reveal five predisposing factors, namely: eligibility, staffing guidelines, course streamlining, workforce surplus management, and alternative programs to be determinants of senior high school readiness among college teachers and higher education institutions that wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Furthermore, there are still teachers who are not ready for senior high school. To note, 18.6% indicated that they are not ready, 2.8% expressed that they are uncertain and partially ready, and 4.3% did not give any comment on the survey given [12]. Also, Chua [13] highlighted that teachers were not ready during the implementation of the senior high school.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are still teachers who are not ready for senior high school. To note, 18.6% indicated that they are not ready, 2.8% expressed that they are uncertain and partially ready, and 4.3% did not give any comment on the survey given [12]. Also, Chua [13] highlighted that teachers were not ready during the implementation of the senior high school.…”
Section: Discussionmentioning
confidence: 99%
“…Roman (2019) argued that the adherence of the educational institution to the mandate of curriculum implementation in terms of program administration, resources, facilities, and equipment facilitates effective implementation. Acosta and Acosta (2016) reported that higher education institutions' readiness for the new structure as well as ensuring a smooth transition and successful implementation of the new program could be measured in terms of eligibility, staffing guidelines, course streamlining, reclassification of teachers, curriculum realignment among others.…”
Section: Introductionmentioning
confidence: 99%
“…It is also imperative to note the preparation being undertaken by higher education institutions as senior high school is imbedded in the curriculum. Acosta & Acosta (2016) identified five factors as determinants of the readiness to implement the senior high school program: "eligibility, staffing guidelines, course streamlining, workforce surplus management, and alternative programs." I Moreover, another related current issue that makes the program's foundation questionable is Programme for International Student Program (PISA) 2018 results in which the country ranks last in Reading with 340 points, and second to the last, in Mathematics with 353 points and following are the key elements to deal with, to perform the critiquing and elucidating process properly providing insights to curriculum development and educational policy formulation.…”
Section: A Introductionmentioning
confidence: 99%